Waived Consent in Perinatal/Neonatal Research—When Is It Appropriate? - Rich, Wade D.; Katheria, Anup C. (Frontiers in Pediatrics, 2019)
Abstract Informed consent is a process ensuring that subjects enrolled in research are appropriately informed of the risks and beneﬁts. While this process is well defined when it is possible and practical to obtain consent prior to the research intervention, it can be less clear in cases of deferred or waived consent. Defining minimal risk, such as when research is attempting to determine which of two currently practiced interventions is safest and/or most effective, is critical to moving forward in establishing appropriate care in newborns. For perinatal/neonatal research the challenge lies between the ethical justification for approaching women in labor or under medication versus the scientific integrity of excluding a number of subjects that may potentially benefit the most from an intervention. Researchers must work with their IRBs as well as families who have participated in trials to determine the most appropriate method for obtaining informed consent from expectant parents. Ultimately clinical researchers and IRBs need to find a middle ground for the appropriate use of deferred or waived consent.